The Young, The Old and the Blessed: Corporate Bodies and Elite Reproduction in Roman Asia Minor - Eckhardt, Benedikt (Classica et Mediaevalia, 2023)
The article traces the impact of Roman rule on the organisational history of Asia Minor through a comparative study of three well-attested institutions: associations of young men (neoi) tied to the gymnasium, councils of elders (gerousiai) that could claim authority and decision-making capacity in their respective cities, and groups of initiates (mystai) who acted on behalf of their cities in public settings. While their Hellenistic origins would suggest a clear-cut distinction between civic institutions such as the neoi and private associations such as the mystai, their operations and status in the Roman period appear remarkably similar, and are difficult to classify within a traditional pri- vate/state binary. It is argued here that two features of Roman rule, the reliance on civic elites and the use of legal privileges for certain kinds of associations, created the condi- tions for wide-ranging institutional change, driven by a combination of Roman administrative input and local agency.